Crystal structure of (2,6-diisopropyl-phenyl)-[6-(2,6-dimethyl-phenyl)- pyridin-2-yl-methylene]-aminopalladium(II) dichloromethane trisolvate, Pd(C26H30N2)Cl2 · 3CH2Cl2 - Maisel H.; Keller S.; Irrgang T.; Kempe R. (Zeitschrift für Kristallographie - New Crystal Structures, 2005)
C29H36Cl8N2Pd, orthorhombic, P212121 (no. 19), a = 16.5460(8) Å, b = 17.995(1) Å, c = 11.817(1) Å, V = 3518.5 Å3, Z = 4, Rgt(F) = 0.037, wRref(F2) = 0.099, T = 193 K.